Television programming on private Algerian channels under the 2014 legislation - Dahbia AIT KACI (Social Sciences Journal, 1970)
Televisional programming is, actually, from the most important domain regarding those areattending for preparing the programmes’ networks for channels in their feverish competitions to raisethe percentages of watching and augment their interests in the advertisement market, although expertsspecialist in information sciences have expected that the television is coming to an end as a mediumable to do that because of the technological revolution and the international market’s requirements.When on the other hand, the Arabic televisions, including the Algerian one, are still at the beginningof the way especially because of it’s a new dealing with private channels. Connecting with this optic,our study seeks defining the legislative’s basicsof televisional programming about private channelsand how they are adapted with the new media lawand the Audiovisual activity 2014 in Algeria, ourobject is to find the difference characteristics, between the private channels and the old publictelevisionمقد